Numerical investigation on cooling performance of oil cooled PMSM jacket design with vertical straight fin design - Thangaraju S.K.; Munisamy K.M.; Rajoo S. (Elsevier B.V., 2023)
Computational fluid dynamics; Fins (heat exchange); Permanent magnets; Coil temperature; Computational fluid dynamic; Cooling performance; High speed generators; Jacket cooling; Numerical investigations; Oil coolant; Operating condition; Permanent magnets synchronous machines; Straight fins; Cooling